KERAGAAN KESEMPATAN KERJA DI SKTOR PERTANIAN DAN PENGARUHNYA TERHADAP PENDAPATAN RUMAH TANGGA PEDESAAN - AMAR K. ZAKARIA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
The Performance of Labor Opportunity on Agriculture Sector Toward RuralHousehold to Increase of Income Effects. The study had done on July, 2005 in Tarusa andKalabeso villages, Sumbawa district, West Nusa Tenggara. In general, this study aim’s toobserve degrees of labor on several of farming activities and farmer’s income. Theresearch using descriptive methods with explanatory analysis to prepare cross table.Primary data were collected from 60 farmers with direct interview. The result of studyshowed that degrees of family labor on farming activities were reached 47 – 56 percentfrom totally of labor use. While the farming on low land was reached 39 – 46 percent usingfamily labor, upland farming (41 – 53%), estate farming (42 – 52%) and livestock (100%).Based on totally of income of farmer’s household from agricultural had biggestcontribution, there are 79 – 87 percent.